Bond behaviour of stainless-clad bimetallic rebar in concrete. (March 2022) - Ban, Huiyong; Chen, Zijian; Xiang, Yong; Li, Zhaodong
Abstract: Stainless-clad (SC) bimetallic rebar combines benefits in terms of both high corrosion resistance and low cost, and therefore has great potential for usage in infrastructure engineering. In order to study the bond behaviour of the SC bimetallic rebar in concrete, a series of tests are carried out and presented herein, with various parameters such as anchorage length, diameter of stirrup and cover thickness being incorporated. Based on the test results, the failure modes, bond-slip curves, bonding strength, residual strength of bond and corresponding slippage are obtained, on which effects of the various parameters are clarified. Comparisons of the bond slip relations of the SC bimetallic rebar with that of ordinary hot-rolled conventional mild steel and stainless steel ones as well as that given in national standards are carried out. Finally, a constitutive relationship model and design suggestions for the bond between the SC bimetallic rebar and concrete are developed, which may provide valuable reference for their use in practice.